iNKT Cells and Their Potential Lipid Ligands during Viral Infection - Opasawatchai, Anunya; Matangkasombut, Ponpan (Frontiers in Immunology, 2015)
Invariant natural killer T (iNKT) cells are a unique population of lipid reactive CD1d restricted innate-like T lymphocytes. Despite being a minor population, they serve as an early source of cytokines and promote immunological crosstalk thus bridging innate and adaptive immunity. Diseases ranging from allergy, autoimmunity, and cancer as well as infectious diseases, including viral infection, have been reported to be influenced by iNKT cells. However, it remains unclear how iNKT cells are activated during viral infection, as virus derived lipid antigens have not been reported. Cytokines may activate iNKT cells during infections from influenza and murine cytomegalovirus (MCMV), although CD1d dependent activation is evident in other viral infections. Several viruses, such as dengue virus (DENV), induce CD1d upregulation which correlates with iNKT cell activation. In contrast, Herpes simplex virus type 1 (HSV-1), Human immunodeficiency virus (HIV), Epstein-Barr virus (EBV) and Human papiloma virus (HPV) promote CD1d downregulation as a strategy to evade iNKT cell recognition. These observations suggest the participation of a CD1d-dependent process in the activation of iNKT cells in response to viral infection. Endogenous lipid ligands, including phospholipids as well as glycosphingolipids, such as glucosylceramide have been proposed to mediate iNKT cell activation. Pro-inflammatory signals produced during viral infection may stimulate iNKT cells through enhanced CD1d dependent endogenous lipid presentation. Furthermore, viral infection may alter lipid composition and inhibit endogenous lipid degradation. Recent advances in this field are reviewed.